2018
DOI: 10.1016/j.athoracsur.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4-Related Disease Mimicking an Anterior Mediastinal Tumor

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is an immune-mediated collection of disorders that were once thought to be unrelated but are increasingly being recognized as a single entity. The tumor-like swelling of the involved organ, a storiform pattern of fibrosis, and a serologic elevation of IgG4 can lead to the diagnosis of IgG4-RD. The usual organs affected are the pancreas, biliary tract, and salivary and lacrimal glands. There have been few reports of intrathoracic cases, which usually have pulmonary le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…However, the tumor present in our case study was heterogeneous, whereas that reported by Iguchi and colleagues [4] was homogeneous. In the report of Kang and colleagues [5], the anterior mass shadow caused by IgG4-RD was a cystic mass with wall calcification, whereas our case demonstrated a solid shadow. These disparities indicate that isolated anterior mediastinal mass caused by IgG4-RD may be associated with several types of shadow, as well as with shadows in other affected organs.…”
Section: Commentcontrasting
confidence: 53%
See 1 more Smart Citation
“…However, the tumor present in our case study was heterogeneous, whereas that reported by Iguchi and colleagues [4] was homogeneous. In the report of Kang and colleagues [5], the anterior mass shadow caused by IgG4-RD was a cystic mass with wall calcification, whereas our case demonstrated a solid shadow. These disparities indicate that isolated anterior mediastinal mass caused by IgG4-RD may be associated with several types of shadow, as well as with shadows in other affected organs.…”
Section: Commentcontrasting
confidence: 53%
“…In addition, some investigators have reported various types of lung disease accompanying systemic IgG4-RD [2]. However, to date there have been only a small number of reports describing an isolated anterior mediastinal mass caused by IgG4-RD [4,5]. We treated a patient with IgG4-RD exhibiting isolated anterior mediastinal mass that mimicked thymoma, and the mass was revealed to have a high level of [ 18 F]-fluoro-2-deoxy-D-glucose (FDG) accumulation.…”
mentioning
confidence: 99%
“…In a French study of 25 patients with IgG4‐related disease, 3 (12%) patients had pulmonary involvement, while none had mediastinal fibrosis . There have been only a few reports of occurrence in the anterior mediastinum …”
Section: Discussionmentioning
confidence: 99%